Comparative analysis of deferasirox and deferiprone iron chelator on the growth pattern of Bengali β-thalassemia major children of West Bengal, India - Isita Tripathy,; Panja, Amrita; Rajarshi Basu, (Asian Journal of Medical Sciences, 2022)
Background: Ineffective erythropoiesis and excessive red blood cell transfusions are the major source of iron overload in case of thalassemia major patients. It is mainly accountable for the growth retardation, morbidity, and mortality in patients with beta thalassemia major. The availability of effective iron chelators and proper knowledge regarding the iron toxicity can significantly improve the rate of survival in thalassemia patients. Aims and Objectives: The study was done to compare the efficacy and safety of the deferiprone (DFP) with deferasirox (DFX) in regulating the growth pattern among the thalassemia major patients. Materials and Methods: The height and weight were plotted on the World Health Organization recommended growth charts for 0–5 years and 5–19 years old boys and girls during the follow-up visits. Comparison between the role of DFP versus DFX was evaluated by t-test. Results: There is no statistically significant (P=0.11 in males and P=0.06 in females) difference between DFP versus DFX while considering height velocity. A similar observation was obtained in case of weight velocity (P=0.78 in males and P=0.56 in females) and basal metabolic index (BMI) index (P=0.44 in males and P=0.53 in females). Conclusion: Both DFX and DFP have no significant correlation in regulating the height, weight, and BMI of thalassemia children.